Pattern formation of metal–oxide hybrid nanostructures via the self-assembly of di-block copolymer blends. Issue 40 (25th July 2019) - Jung, Dae Soo; Bang, Jiwon; Park, Tae Wan; Lee, Seung Hyup; Jung, Yun Kyung; Byun, Myunghwan; Cho, Young-Rae; Kim, Kwang Ho; Seong, Gi Hun; Park, Woon Ik
Abstract : Unusual pattern generation of hybrid nanostructures can be achieved via the microphase separation of blended di-BCPs. We present a useful method which is capable of forming uniform hybridized BCP patterns consisting of metal and nonmetal materials. Abstract : The templated self-assembly of block copolymers (BCPs) with a high Flory–Huggins interaction parameter ( χ ) can effectively create ultrafine, well-ordered nanostructures in the range of 5–30 nm. However, the self-assembled BCP patterns remain limited to possible morphological geometries and materials. Here, we introduce a novel and useful self-assembly method of di-BCP blends capable of generating diverse hybrid nanostructures consisting of oxide and metal materials through the rapid microphase separation of A–B/B–C BCP blends. We successfully obtained various hybridized BCP morphologies which cannot be acquired from a single di-BCP, such as hexagonally arranged hybrid dot and dot-in-hole patterns by controlling the mixing ratios of the solvents with a binary solvent annealing process. Furthermore, we demonstrate how the binary solvent vapor annealing process can provide a wide range of pattern geometries to di-BCP blends, showing a well-defined spontaneous one-to-one accommodation in dot-in-hole nanostructures. Specifically, we show clearly how the self-assembled BCPs can be functionalized via selective reduction and/or an oxidation process, resulting in the excellent positioning of confined silica nanodots into each nanospace of a Pt mesh. These results suggest a new method to achieve the pattern formation of more diverse and complex hybrid nanostructures using various blended BCPs.